Why do we need to empower university staffs and students for tackling the non-communicable diseases? - Supriyati Supriyati; Anggi Lukman Wicaksana; Esthy Sundari; Heny Suseani Pangastuti; Fatwa Sari Tetra Dewi (Faculty of Medicine, Public Health, and Nursing, Universitas Gadjah Mada, 2021)
Non-communicable diseases (NCDs) are a major cause of death in Indonesia and worldwide. Yogyakarta has the highest prevalence of cancer in Indonesia. Besides, Yogyakarta has high prevalence of diabetes mellitus and other NCDs. The prevention and control of NCDs are direly needed in Yogyakarta. Universitas Gadjah Mada (UGM) is the oldest university in Yogyakarta and has a large number of university staff members and students. This study aimed to empower university staff and students of UGM in the health promotion programs for tackling NCD risk factors through the Health Promoting University initiative. This was a participatory action research that was conducted in UGM, Yogyakarta. A total of 299 respondents (university staff and students in second year) were involved in the need’s assessment survey. Data were collected through online questionnaire and analyzed descriptively. Additionally, advocacy, training, small group discussion, seminars, discussion on WhatsApp group, as well as developing posters for healthy diet, hand washing, physical activities, and smoking behavior were done as the follow-up of the need’s assessment. The need’s assessment showed that most respondents had a poor knowledge on the NCDs and its risk factors (74%), poor knowledge on the smoke free campus (80%), had insufficient vegetables consumption (83%), had insufficient fruit consumption (68%), and had physically inactive behavior (52%). Furthermore, group discussions with the students improved their awareness on the NCD problems among students. Also, training for the university staff members improved their knowledge and skills related to the NCD risk factors’ measurement. The university staff and students’ knowledge and practice concerning the NCD risk factors prevention were poor. Therefore, the Health Promoting University initiative is a good way to empower them about the NCD risk factors prevention.